2009
DOI: 10.1073/pnas.0809180106
|View full text |Cite
|
Sign up to set email alerts
|

Functional motifs in the (6-4) photolyase crystal structure make a comparative framework for DNA repair photolyases and clock cryptochromes

Abstract: Homologous flavoproteins from the photolyase (PHR)/cryptochrome (CRY) family use the FAD cofactor in PHRs to catalyze DNA repair and in CRYs to tune the circadian clock and control development. To help address how PHR/CRY members achieve these diverse functions, we determined the crystallographic structure of Arabidopsis thaliana (6-4) PHR (UVR3), which is strikingly (>65%) similar in sequence to human circadian clock CRYs. The structure reveals a substrate-binding cavity specific for the UV-induced DNA lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(163 citation statements)
references
References 60 publications
(66 reference statements)
5
156
1
1
Order By: Relevance
“…His366 in PhrB is stabilized by van der Waals contacts with Leu370 and Met410 (Fig. 3A), whereas the homologous His in eukaryotic photolyases is stabilized by a hydrogen bonding network (15,22). The orientation of His366 in PhrB, however, matches with the homologous His residue of Drome (6-4) PL (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…His366 in PhrB is stabilized by van der Waals contacts with Leu370 and Met410 (Fig. 3A), whereas the homologous His in eukaryotic photolyases is stabilized by a hydrogen bonding network (15,22). The orientation of His366 in PhrB, however, matches with the homologous His residue of Drome (6-4) PL (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In a structural alignment (23) of PhrB and two eukaryotic (6-4) photolyases (15,22), we have identified 34 identical amino acids, 10 of which are conserved to 99-100% in all FeS-BCPs. Three of these amino acids cluster together in the His365-His366-X-X-Arg369 motif.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings shed new light on the functional importance of the CRY1-PHR(313-426) and the CTD in the clock mechanism. Several previous studies identified a subset of common motifs and sites, including nuclear localization sequences, coiled-coils, phosphorylation sites of CK1⑀, GSK3␤, MAP kinase, and AMP-activated protein kinase (44,45,47,49,50,(53)(54)(55)(56), and surely additional motifs remain yet to be identified. The functional significance of these various sequences and structural features in CRY function will need to be tested using the assays developed in this study.…”
Section: Genetic Complementation Of Cry1 In Cry-deficient Cells Provimentioning
confidence: 99%
“…Based on known structure and domain functions of PHL/CRY proteins (18,19,44), we divided CRY1 and -2 proteins into four regions, namely A, B, C, and D ( Fig. 2A; supplemental Fig.…”
Section: Cry1-phr(313-426) Ismentioning
confidence: 99%
“…The structure and reaction mechanisms of photolyases have been intensively studied in the last decade, providing us with plentiful data on their function. Photolyases have two types of chromophoric co-factors that are used for photoreactivation (Huang et al, 2006;Ozturk et al, 2008;Hitomi et al, 2009). One chromophore is FADH -, the two electron reduced form of FAD, while the second one can be either methenyltetrahydrofolate (MTHF) or 7,.…”
Section: Photoreactivation By Photolyasesmentioning
confidence: 99%